Description of Coeliccia lephuocdieui sp. nov. from the Central Highlands of Vietnam (Odonata: Zygoptera: Platycnemididae) with notes on its congeners - Phan, Quoc Toan; Ngo, Quoc Phu; Bui, Anh Phong (Zootaxa, 2020)
Coeliccia lephuocdieui sp. nov. (holotype ♂, 14.2586N, 108.3786E, Kon Ka Kinh National Park in Ayun Commune, Mang Yang District, Gia Lai Province, the Central Highlands of Vietnam) is described and illustrated for both sexes. A comparison of the new species with Coeliccia scutellum Laidlaw, 1932 and C. yamasakii Asahina, 1984 is provided with notes on the morphological variation of the Vietnamese C. scutellum. The female of C. yamasakii is described for the first time.